West Midlands Major Trauma Centre Theatre Practitioner Collaborative. Issue 11 (November 2016) - Doyle, G
The following article highlights the establishment of the West Midlands Major Trauma Centres (MTC) in April 2012 and specifically the West Midlands Major Trauma Centre Theatre Practitioner Collaborative in June 2013. The article looks at the involvement of theatre practitioners working as an integral part of the emergency department and supporting anaesthetists when attending alerts. There is a summary of clinical responsibilities, mentorship opportunities and the educational programme associated with the role. The MTC collaborative ensures that there is support for individual centres with regular meetings covering clinical and educational issues as well as conducting cross site skill programmes. The collaborative are working toward a formal approach to a higher educational institution, to consider establishing a post graduate training module and to prepare theatre practitioners for the role in the emergency department.